Nursing Students’ Clinical Confidence In Caring Tuberculosis: Indonesian Version Of The U.S Tuberculosis Curriculum Consortium Survey Using Rasch Analysis - Theresia, Theresia; Mei Huang, Hsiu; Yu Liu, Chieh; Ying Lee, Tzu (Poltekkes Kemenkes Surakarta, 2023)
Background: Nursing students who are prepared in clinical practicums to comprehend the knowledge, reflect their beliefs about tuberculosis instruction, and perceive their abilities in caring for tuberculosis patients are also at risk. Nursing students’ clinical confidence in caring for tuberculosis patients is essential to be assessed. Knowledge, beliefs, and clinical confidence, as unidimensional constructs based on Bandura’s theory of self-efficacy, had been used in the US National Tuberculosis Curriculum Consortium (NTCC) survey for nursing students. This study's objective was to investigate the Indonesian version of the NTCC survey among nursing students' experiences caring for tuberculosis patients. Methods: A quantitative study with cross-sectional using an online survey among 250 students 1st to 3rd-yearrd year students in one faculty of nursing in Banten, Indonesia. Prior to data collection, NTCC surveys were translated backward and forward, reviewed by experts, and tested in a pilot project. Results: Internal consistency using Rasch analysis on each subscale showed good results and gave strong evidence that three subscales are unidimensional. There was an item separation index and reliability score, in that order: knowledge about tuberculosis (8.68 and 0.99), beliefs regarding tuberculosis instructions (6.50 and 0.98), and clinical confidence in caring for tuberculosis patients (6.29 and 0.98). Conclusion: The Indonesian version of the NTCC survey has excellent internal consistency. This instrument might be improved since the original instrument is 13 years old and there is a cultural gap between the US and Indonesia. Moreover, this instrument might be needed for improving tuberculosis teaching in the nursing curriculum in Indonesia.